Development of the DNA-based voltammetric biosensor for detection of vincristine as anticancer drug - Abbasi, Mahmoud; Alsaikhan, Fahad; Obaid, Rasha Fadhel; Jahani, Shohreh; Biroudian, Saeed; Oveisee, Maziar; Arab, Mohammad Reza; Aramesh-Boroujeni, Zahra; Foroughi, Mohammad Mehdi (Frontiers in Chemistry, 2023)
In the article presented herein, a deoxyribonucleic acid (DNA) biosensor is introduced for Vincristine determination in pharmaceutical preparations based on the modification of screen printed electrode (SPE) with double-stranded DNA (ds-DNA), polypyrrole (PP), peony-like CuO:Tb3+ nanostructure (P-L CuO:Tb3+ NS). The developed sensor indicated a wide linear response to Vincristine concentration ranged from 1.0 nM to 400.0 μM with a limit of detection as low as .21 nM. The intercalation of Vincristine with DNA guanine led to the response. The optimized parameters for the biosensor performance were ds-DNA/Vincristine interaction time, DNA concentration and type of buffer solution. The docking investigation confirm the minor groove interaction between guanine base at surface of or ds-DNA/PP/P-L CuO:Tb3+ NS/SPE and Vincristine. The proposed sensor could successfully determine Vincristine in Vincristine injections and biological fluids, with acceptable obtains.